FROM THE PHILOSOPHY TO THE SOCIOLOGY OF WORK - Slijepčević, Dušanka P. (Politeia, 2025)
Review of the book Lars Fr. H. Svendsen – Philosophy of Work (trans. Radoš Kosović), Geopoetika Publishing, Belgrade, 2012, p. 156.